1996
DOI: 10.1108/19355181199600005
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for Improving Security of Local Area Networks

Abstract: Security of data and information has always been a concern for business organizations. With recent trends towards down‐sizing and the implementation of Local Area Networks, the necessity for the development of carefully formulated policies and procedures for data security has taken on a new emphasis. Auditors are responsible for the verification of security measures, as well as recommending corrective actions or proper measures when risks and exposures are found. The authors provide an overview of the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Researchers working on online learning have identified several challenges associated with webbased courses, including the lack of immediate response to students' questions or concerns, and students' feeling of isolation from the instructor and other students enrolled in class. [1][2][3][4][5][6] Song and colleagues found that a familiarity with online technologies and proper time management contributed to student satisfaction in an online environment. 2 They also indicated that a lack of student understanding of course objectives lead to students' dissatisfaction in a web-based course.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers working on online learning have identified several challenges associated with webbased courses, including the lack of immediate response to students' questions or concerns, and students' feeling of isolation from the instructor and other students enrolled in class. [1][2][3][4][5][6] Song and colleagues found that a familiarity with online technologies and proper time management contributed to student satisfaction in an online environment. 2 They also indicated that a lack of student understanding of course objectives lead to students' dissatisfaction in a web-based course.…”
Section: Introductionmentioning
confidence: 99%